Punitive Damages in Unfair Dismissal Cases: Lessons from Malaysia and New Zealand - Abdul Shukor, Siti Fazilah; Abd Razak, Siti Suraya (Indonesian Comparative Law Review, 2023)
Employers tend to dismiss employees without proper grounds, in bad faith or fail to follow procedure prescribed under law. An employee that has been dismissed unfairly can bring an action against the employer for unfair dismissal. Damage is the most sought remedy of the employee for unfair dismissal claims. Punitive damage is a form of monetary remedy awarded by the court in addition to the actual damage to the aggrieved party. Punitive damage is awarded as a punishment to the wrongdoer. Punitive damage has become the remedy in both Malaysia and New Zealand. The objective of this study is to analyse the punitive damage awarded by the Malaysian Industrial Court and New Zealand Court in unfair dismissal cases. This study employed a qualitative method with reference to journal articles, relevant statutory laws and case laws on unfair dismissal cases with punitive damage as an award. The findings show that punitive damages in unfair dismissal cases have been awarded by the Malaysian industrial court and New Zealand court against employers on the grounds that the dismissals were made under bad faith. This study is significant as it expands the application of punitive damage in unfair dismissal cases and improve the system’s legal certainty.